Living in the tide of change: explaining Japanese subjective health from the socio-demographic change - Hitokoto, Hidefumi; Tanaka-Matsumi, Junko (Frontiers in Psychology, 2014)
Today, countries around the world are caught in the tide of change towards Gesellshaft, or individualistic socio-demographic condition. Recent investigations in Japan have suggested negative impacts of change on emotional and motivational aspects of the Japanese self (Norasakkunkit, Uchida, and Toivonen, 2012; Ogihara and Uchida, 2014). Building on previous findings, in Study 1, we measured socio-demographic change towards individualistic societal condition during 1990 to 2010—two decades marked by great economic recession—at the levels of prefecture and city using archival data. In Study 2, we tested whether Japanese adults’ general health, satisfaction with life, self-esteem, and perceived social support were negatively predicted by the change using social survey. Results of hierarchical linear modeling showed small but unique negative effects of the change on several health measures, suggesting that this change had an impact on health, above and beyond individual personality traits and demographics. Additionally, interdependent happiness, the type of cultural happiness grounded in interdependence of the self (Hitokoto and Uchida, 2014), showed an independent positive relationship with all aspects of health examined. Implications for health studies in changing socio-demographic condition are discussed in the context of Japanese society after economic crisis.